Analisis Kemampuan PCK Calon Guru Melalui Pembuatan PaP-eRs - Suci Nurmatin (Pusat Penelitian dan Pengabdian Kepada Masyarakat (P3M) STAI, 2023)
A study involving final year students who are carrying out PPL. The purpose of this study was to analyze the Pedagogical Content Knowledge (PCK) ability of prospective teachers in reflecting on learning after carrying out learning practices. The study is focused on making Pedagogical and Professional Repertoires (PaP-eRs). PaP-eRs are narratives of learning activities created by prospective teachers. The making of the narrative is intended so that prospective teachers can reflect on their learning. The research subjects were six prospective teachers who were carrying out PPL in schools that had been determined by the study program. The instrument used as a data collection tool in this study was the PaP-eRs. The collected PaP-eRs were then analyzed using the PaP-eRs analysis format. The results of the PaP-eRs analysis show that the narrated learning activities include preliminary activities, core activities and closing activities. However, each activity is only narrated in outline so that the narrative cannot be used as a reflection of learning. This shows that the ability of PCK prospective teachers to reflect on learning through creating learning narratives (PaP-eRs) is still low